Analisis Hasil Menulis Mengembangkan Hikayat Menjadi Cerpen Kelas X - Septiana, Nanda Fauzi; Bowo, Sigit Arif (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
This research aims to describe (1) the results of writing developing a saga into a short story for class X SMA Batik 2 Surakarta, (2) factors that become obstacles to writing to develop a saga into a short story for class X SMA Batik 2 Surakarta, and (3) a solution to overcome writing obstacles to develop a saga into a short story for class X SMA Batik 2 Surakarta. This type of research is qualitative research. Data collection techniques use interview and documentation techniques. Data validity using source triangulation techniques. The data analysis technique uses Miles and Huberman's interactive analysis technique. The results of this research show that: (1) The results of writing short stories from 39 students obtained the highest student score of 91, the lowest score of 75, with an average student score of 83. Assessment of several assessment aspects, namely theme, grammar, punctuation and neatness of writing, character/characterization, plot, and mandate. Based on the assessment aspect, 209 data were found and the most errors occurred in the grammatical aspect. Uniquely, no errors were found in the plot and message aspects so that students were able to create the plot and message in the story. (2) factors that become obstacles in students' writing are lack of writing practice, lack of feedback on student assignments, students when writing stories pay less attention to their writing, lack of understanding regarding the material, the Indonesian language learning methods used by teachers are less varied, lack of ideas from students in developing the storyline, lack of understanding of the contents of the saga, and lack of time to complete assignments. (3) solutions to overcome student obstacles, namely increasing the frequency of writing practice, applying feedback techniques to assignments appropriately, providing examples of good and correct use of Indonesian in learning, providing additional discussions outside of learning, using more varied learning methods, increasing frequency of reading and exploration, and providing additional hours related to writing assignments.